Prevalence of Gestational Diabetes Mellitus, Maternal and Neonatal outcomes in a Peripheral Hospital in North India - Choudhary, Naiyma; Rasheed, Mohd; Aggarwal, Vivek (International Journal of Research in Medical Sciences, 2017)
Background: Gestational diabetes mellitus (GDM) is a well-known medical entity which should be diagnosed at the earliest to prevent adverse maternal and neonatal outcomes due to hyperglycemia. Methods: This study was done in patients attending antenatal OPD in a peripheral hospital in North India. A total of 569 patients diagnosed as GDM were included in the study out of 6321 who attended the antenatal clinic. Results: The prevalence of gestational diabetes mellitus was found to be 9%. Gestational hypertension was seen in 29.35% of patients. The percent of babies who were admitted to NICU was 29.35%. Conclusions: These results stress the need for early detection and treatment of GDM to prevent adverse outcomes.